Tradition in the Context of Philosophical Work - Proleiev, Sergii (Sententiae, 2025)
The article examines the theoretical relevance of the concept of national philosophical tradition, which is considered a distinctive characteristic of the existence of philosophy in the context of a particular national culture and society. The author criticizes two common ways of understanding national philosophical traditions. The first considers such a tradition as the highest level of creative achievement of philosophical thought, which determines the historical development of philosophy as such. The second associates national philosophical tradition with manifesting the original foundations of national life (culture). In contrast to these approaches, the following position is proposed: the national philosophical tradition is formed by the effect of the integration of philosophy into the national culture, i.e., by using it to solve the most important problems of the development of a given society. Tradition is, first of all, not a look back but a movement forward. Based on understanding tradition as a universal way of passing on cultural experience, philosophical tradition seeks to answer the question, "How is philosophical work passed on, reproduced, and developed? This question and the meaning of philosophical tradition can only be understood by considering a complex number of other questions and concepts that characterize the philosophical life of a particular country: philosophical community, institutions, education, communication, culture, social influence of philosophy, etc. Having a tradition is not in itself a positive thing. It can be of inferior quality, simulative, weak, unoriginal, etc. In addition, tradition imposes certain substantive limitations – it is characterized by a certain inertia of thought and the temptation to follow already mastered and proven ways of thinking. Therefore, the development of philosophical work presupposes following tradition and constant revision.